Effect of Saline Waters on Pearl Millet Under Drought - Garg, B K; Vyas, S P; Kathju, S; Lahiri, A N (Annals of Arid Zone, 2016)
A study on the influences of saline waters (composition similar to local ground waters) at the critical pre-flowering stage of pearl millet (cv. BJ-104) crop, under drought and undroughted conditions, revealed that a significantly higher dry matter production and grain yield can be achieved if the water stress is avoided through irrigation with sub-standard waters (160 me }-1). The derangements in the levels of a number of leaf metabolites, induced by water stress, were not norma- listed even seven days after irrigation with saline waters. Notwithstanding the increasing adverse effects, found in most cases with higher salt concentration, metabolic derangements were far less where drought was avoided through saline water irrigation .